PEMBUATAN PERANGKAT LUNAK MODEL SIMULASI PENGOPERASIAN WADUK WONOGIRI UNTUK PENGENDALIAN BANJIR DI WILAYAH SUNGAI BENGAWAN SOLO HULU - , ADIB FARIKHA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wonogiri reservoir has water catchment areas (DTA) as many as 10 watershed (DAS), with Keduang DAS is the largest watershed of DTA of Wonogiri Reservoir.Keduang DAS channels large sedimentary so that affect on the reduction of the volume of the reservoir catchment. To solve the sedimentation problem, it has been built a new spillway and closure dike that separates the reservoir catchment into two parts, the Main Reservoir (MR) and Sediment Storage Reservoir (SSR). Previously it has been done a research about the development of the hydrologic-hydraulic software using visual basic software for flood control, but not in accordance with the current conditions. Therefore, it needs to make the development of new software in accordance with the circumstances that exist at of Wonogiri Reservoir. Software of Wonogiri Reservoir simulation operation model for flood control in the area of the Solo River was created using Microsoft Visual Studio software and Microsoft Access. This software simulating reservoir flood routing calculations to obtain the appropriate spillway operation pattern so that the reservoir in a safe condition. That operation pattern are spillway recommendations which will operate (only new spillway or old spillway will operate too) along the door aperture height. The result of the software development gives realtime monitoring information on the reservoir. That monitoring data in the form of